2014
DOI: 10.1089/end.2013.0740
|View full text |Cite
|
Sign up to set email alerts
|

Novel Green-Light KTP Laser En Bloc Enucleation for Nonmuscle-Invasive Bladder Cancer: Technique and Initial Clinical Experience

Abstract: The modified technique using a front-firing green-light laser to en bloc enucleate bladder tumors is effective and safe for treatment of NMIBC. Moreover, it may improve the accurate valuation of tumor stage and prediction of postoperative prognosis, although long-term outcomes and prospective clinical trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…Urol Int 2020;104:402-409 DOI: 10.1159/000503734 high as 97% [26] and 100% [27,28]. These studies emphasize the quality of NMIBC resection can be improved with ERBT.…”
mentioning
confidence: 85%
“…Urol Int 2020;104:402-409 DOI: 10.1159/000503734 high as 97% [26] and 100% [27,28]. These studies emphasize the quality of NMIBC resection can be improved with ERBT.…”
mentioning
confidence: 85%
“…Yet, the main disadvantage was the lack of sufficient tissue for pathologic examination [63]. Subsequently, He et al introduced en bloc with a KTP laser using front-firing fibre on 45 patients, showing the feasibility and safety of the procedure [64]. In the prospective, non-randomised study on 158 patients (83 KTP en-bloc and 75 cTURBT) by Chen et al the authors showed that resection with laser was associated with lower complication rates and had shorter duration.…”
Section: En Bloc Using a Green-light Ktp Lasermentioning
confidence: 99%
“…Bei den Kalium-Titanyl-Phosphat-und Lithiumborat-Lasern (KTP, LBO; besser bekannt als Greenlight-Laser) basierten Ansätzen, vor allem ohne side fire-Faser, ist bei der Anwendung darauf zu achten, keine unkontrollierten und ungewollten Gewebsschäden außerhalb des Resektionsareals zu verursachen, da Laserenergie auf dieser Wellenlänge von 532 nm nicht durch das Spülmedium abgebremst wird [33]. Für die KTP/LBO-Laser wurden Energieleistungen von 30 [34]…”
Section: Die Laser-erbt (L-erbt)unclassified